T CEP, U UMI, Z SCO – MIRA-TYPE VARIABLES WITH CYCLIC PERIOD CHANGES - Marsakova, V. I. (Одеські астрономічні публікації, 2013)
Period and amplitude changes of three Mira-type variables have been analyzed. Characteristics of long-term cyclicity were obtained